Brain Abscess Formation: A Delayed Complication of Carotid Blowout Syndrome Treated by Self-Expandable Stent-Graft - Chang, F.-C.; Lirng, J.-F.; Tai, S.-K.; Luo, C.-B.; Teng, M.M.H.; Chang, C.-Y. (American Journal of Neuroradiology, 2006)
SUMMARY: A patient with hypopharyngeal cancer developed carotid blowout syndrome (CBS) treated by self-expandable stent-graft in the left carotid artery. CT scan for progressive right hemiparesis 4 months later showed multiple left cerebral abscesses and left carotid thrombosis. Although deployment of stent-grafts for CBS can achieve initial hemostasis in patients with head-and-neck cancer, the placement of a stent-graft in a field of necrosis and infection is associated with poor long-term outcome. We recommend the use of prophylactic antibiotics if endovascular foreign materials are placed in a contaminated field.